Educational Multi-Purpose Kit for Coding and Robotic Design - Thongpool, Atikhun; Hormdee, Daranee; Chutipakdeevong, Raksit; Tansakul, Wasan (Proceedings ... Asia-Pacific Signal and Information Processing Association Annual Summit and Conference APSIPA ASC ... (Online), 2022)
Nowadays, there has been a rapid evolution and transformation of technology. Many innovative technologies have emerged including artificial intelligence, biomedical engineering, automation systems, quantum computing, big data, blockchain, etc. These emerging technologies have also transformed our lifestyles. This transformation has then inevitably required a new set of skills; Computational Thinking/Logical Thinking which can be compiled into Coding skills. Several novel educational media and teaching materials have been promoted. Current educational kits in the market can be classified into 3 main categories. These structures vary from physical kits vs virtual kits vs hybrid kits, while coding styles vary from block-based vs text-based. This paper presents an educational multi-purpose kit for coding and robotic design which has a hybrid kits structure with block-based coding style. Its connection scheme has been designed as wired/wireless plug-and-play via magnetic. The implemented prototype could be resilient for various learning activities, including emulating three (touch, hearing and sight) out of five basic human senses via sensors and actuators. A use case on shape recognition, using computer vision, has been illustrated to show how the implemented system works.